The Influence of Product Quality and Customer Reviews on Repurchase Intention Mediated by Customer Satisfaction in Shopee E-Commerce in Pontianak - Muhammad Riyanto Saputra; Helman Fachri (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to examine the influence of product quality and customer reviews on repurchase intention with customer satisfaction as a mediating variable among Shopee users in Pontianak. The research employed a quantitative approach through a survey method. Data were collected from 100 respondents using a Likert-scale questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares. The findings reveal that both product quality and customer reviews have a positive and significant effect on customer satisfaction, while satisfaction itself significantly influences repurchase intention. However, product quality does not directly affect repurchase intention, whereas customer reviews have a positive effect. Customer satisfaction was found to mediate the relationship between product quality and repurchase intention but not the relationship between customer reviews and repurchase intention. These results highlight the crucial role of satisfaction in linking product quality to repeat purchasing behavior and emphasize the importance of credible reviews in shaping consumers’ repurchase decisions. For future research, it is recommended to expand the study area and increase the sample size to enhance representativeness, as well as to include additional variables such as trust, perceived value, and shopping experience to provide a more comprehensive understanding of the factors influencing repurchase behavior in the e-commerce ecosystem.